2020
DOI: 10.1021/acsomega.0c04095
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Periodic Wave Function Approach for the Study of Infinitely Periodic Solid-State Systems. I. Application to the C–H···π(C≡C) Hydrogen Bonding Systems

Abstract: The cyclic periodic wave function (CPWF) approach is applied at the AM1 and PM3 semiempirical levels of approximation to infinitely periodic solid-state systems stabilized by weak CH–pi (C–H···π) interactions between repeat units. The reliability of the AM1 and PM3 methods for modeling C–H···π bonding is first demonstrated using two representative dimer systems: the T-shaped ethyne dimer and the T-shaped propyne dimer. The CPWF method is then applied to two different crystal systems that are stabilized by C–H·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Longer-range interactions are at least partially recovered by the use of our Madelung correction scheme, 40 which corrects both the individual Fock matrix elements as well as the total energy by approximately recovering all interactions between farther neighbors. 40 We have found that using N = 4 suffices for most solid-state systems, 60,61 as long as the intermonomer interactions are weaker than covalent interactions. Even when covalent interactions occur between monomers, we have found that N = 4 often suffices, though using N = 6 in the direction of the covalent interaction will provide greater accuracy for some systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Longer-range interactions are at least partially recovered by the use of our Madelung correction scheme, 40 which corrects both the individual Fock matrix elements as well as the total energy by approximately recovering all interactions between farther neighbors. 40 We have found that using N = 4 suffices for most solid-state systems, 60,61 as long as the intermonomer interactions are weaker than covalent interactions. Even when covalent interactions occur between monomers, we have found that N = 4 often suffices, though using N = 6 in the direction of the covalent interaction will provide greater accuracy for some systems.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is a chemically intuitive approach. The repeat units are chosen to be either the individual molecules within molecular solids or the individual monomer units within polymers, , and are placed at their exact translationally periodic positions, as found in the infinitely periodic crystal, without any built-in periodic boundary conditions (PBCs). For chemists, it is a more intuitive way to study large organic crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our calculation results for the study of infinitely periodic solid-state systems containing very weak CH−pi (C−H•••π) interactions between repeat units are submitted in the previous paper. 47 Our goal in this paper is to continue applying this CPWF approach at the AM1 44 and PM3 45,46 semiempirical levels of approximation to systems containing weak interactions. Thus, we will use our modified MOPAC 25 The conformations of these two polysaccharides are quite complex because of their multiple forms.…”
Section: Introductionmentioning
confidence: 99%